An introduction to medieval philosophy - Martin, C. F. J. (Christopher F. J.) (Edinburgh University Press, 1996)
"Philosophical concepts permeate Medieval history and literature but, until now, there has been no specific introduction to the philosophy of the middle ages. This accessible textbook takes the student step-by-step through the intellectual problems of Medieval thought, explaining the principal lines of argument from Augustine of Hippo (d.430) to the 16th century." "Emphasising the relationship between reason and faith, the author describes how and why Medieval philosophers saw their task as the development of a tradition handed down authoritatively. The first general introduction of its kind, this book will give students from a wide range of disciplines an essential philosophical understanding of the Medieval period."--Jacket